Representations of forest: social anthropological study of a village on the border of the dry deciduous forest in Madagascar - Lindenmann, Katharina (My University, 2008)
Soatany is a village of subsistence farmers in the Menabe central (Madagascar). The village was established mostly by immigrants coming from the south of Madagascar. The current location of the village and its cultivation sites used to be forest territory. The story of the village is the story of a successful transformation of a forest into a prospering village. This is the important background of the local representation of the forest. Soatany is subject to an important internal migration. There is the shared idea by the Malagasies, of «forest »as substructure for a successful installation on the land. The newcomers are taking possession of «open »grounds, which in the perception of the first arrivals, are places reserved for the spreading of their descendants. Because of cultural differences this conict is mostly felt between the ethnical groups living in the village center and the Antandroy living in the hamlets of the village. The village is under an important impact of several conversationalist projects. The NGO Durell Wildlife Conservation Trust initiated the project of the GCF (Gestion Contractuel de la Forêt). The familiy of the fokontany-president has appropriated this project to their advantage. Consequently the project is not perceived as a communal project by the villagers of Soatany but as a private actor in the interest of the fokontany-president family. The cultivation on the village territory is monitored by another NGO called «Fanamby », which controls the expectations of the interdiction of forest deforestation. This monitoring is badly received by all the villagers. The locals feel as to having lost important sovereignty over the village land to the vazaha (foreigners). This constant intervention in their cultivation habits is touching spheres of the utmost importance for the villagers. This situation of the constant arrivals of newcomers and the pressure of the conservationist projects becomes tactile in the recounted stories about blood-thieves representing the image of the vazaha taking away the pure essence of live and persons having risen from the death, as image of the infinite regeneration of the immigrant.
Mémoire de diplôme universitaire : Université de Neuchâtel, 2008